Terence Irwin, Plato's Ethics. Oxford University Press. New York-Oxford 1994. XX + 444 páginas. ISBN 0-19-508645-7 - Sacchi, Mario Enrique (1995)
Fil: Sacchi, Mario Enrique. Investigador independiente